Belirsiz alacak davası - Simil, Cemil (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Özel Hukuk Anabilim Dalı / Özel Hukuk Bilim Dalı, 2012)
Belirsiz alacak davası, Hukuk Muhakemeleri Kanunu'nun 107. maddesinde düzenlenmiştir. Bu hükme göre, davacıdan, davanın açıldığı anda alacağın miktarının veya değerinin belirlenmesinin beklenemeyeceği veya bunun imkansız olduğu hallerde, alacaklı hukuki ilişkiyi ve asgari bir miktar veya değer göstererek dava açabilmektedir. Davacı, yargılama sırasında, karşı taraftan aldığı bilgiden veya delillerin incelenmesinden sonra davalının rızasına veya ıslah yoluna başvurmaya gerek duymaksızın, talebinin miktarını belirleyebilmektedir. Davanın açıldığı anda, miktarı veya değeri belirlenebilen alacaklar için, hukuki yarar yokluğu nedeniyle, belirsiz alacak davası açılamaz.
Undetermined claim lawsuit
Undetermined claim lawsuit is regulated in article 107 of Civil Procedure Law. According to the article, the claimant can file a lawsuit by setting forth the legal relationship and a minimum quantity or value in the situations that determination of the quantity or value of claim is not possible or can not be expected from the claimant at the time of the lawsuit. The claimant, during the proceeding, has the right to define the quantity of the claim after acquiring information from the respondent or examination of the evidences without the need to respondent?s consent or file for amendment. As for the claims whose quantity or value can be determined at the time of the lawsuit, an undetermined claim lawsuit can not be filed due to the lack of legal interest.
Keywords: Belirsiz alacak davası; Undetermined claim lawsuit; Davalar; Cases; Türk Hukuku; Turkish Law